Religious Education as a Safe Learning Space for Mental Health Support: A Multiple Case Study on Pedagogical Dimensions and Practices in Junior High Schools - Risma Putri Rahayu; Syahidin Syahidin; Agus Fakhruddin (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Adolescent mental health is an urgent concern in junior high schools, yet the role of Islamic Religious Education (Pendidikan Agama Islam, PAI) in supporting it remains underexamined. Existing studies emphasize instructional effectiveness, leaving everyday classroom dynamics-teacher-student relationships, atmosphere, and lived learning experiences largely unexplored. This study examined how PAI classes function as psychologically safe spaces and which mental health dimensions emerge most consistently in practice. A qualitative multiple-case study was conducted in three public junior high schools in Bandung, Indonesia (SMPN 4, 14, and 43), drawing on 17 classroom observations and interviews with 13 participants (five PAI teachers, three guidance counselors, and five students). Data were analyzed through an interactive model using hybrid coding that combined a priori categories with emergent subthemes. The analytic framework integrated an indigenous Islamic taxonomy with Keyes' Mental Health Continuum across spiritual, emotional, psychological, social, and biological dimensions. Spiritual and emotional dimensions were most consistently present, whereas the psychological dimension appeared least often and required intensive, individualized engagement. Cross-case analysis revealed a core tension: a programmatic emphasis on spirituality coexisted with low internalization of values, exposing a gap between ritual and lived practice. Safe learning environments emerged where teacher innovation, school religious culture, and Sundanese–Islamic values converged, while peer dynamics and limited instructional time formed structural barriers beyond individual pedagogy. The findings reposition PAI as a pedagogical site for adolescent mental health support and call for school-level interventions targeting structural conditions rather than teacher initiative alone